Comparative Analysis of the Performance of Cryptocurrency, Stocks, and Forex as Investment Alternatives, 2021-2024 - Heru Fendriansyah; Alamsyah Abubakar (Green Publisher Indonesia, 2026)
The purpose of this study is to analyze the performance comparison between cryptocurrency, stocks, and forex as alternative investment assets. This research employs secondary data and a comparative method. The objects of the study consist of the top five assets with the largest market capitalization in each category (cryptocurrency, saham, and forex) for 2024, covering September 2021 to September 2024. Data are monthly closing prices, analyzed via saturated sampling for comprehensive, representative results. Performance is measured using key indicators such as return, risk, and ratios including Sharpe, Treynor, and Jensen. Results show cryptocurrency exhibits superior performance over stocks and forex, with higher returns (19.12% vs. 1.91% for stocks and 0.02% for forex) and optimal ratios: Sharpe (0.83), Treynor (0.1521), and Jensen (0.1705). These metrics highlight cryptocurrency's strong risk-adjusted returns, making it attractive for risk-tolerant investors. However, it carries the highest risk (42.98% vs. 6.42% for stocks and 1.77% for forex), underscoring the need for careful risk management due to its high volatility.